1974
DOI: 10.1085/jgp.64.6.643
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intracellular Free Calcium Concentration during Illumination of Invertebrate Photoreceptors

Abstract: Aequorin, which luminesces in the presence of calcium, was injected into photoreceptor cells of Limulus ventral eye. A bright light stimulus elicited a large increase in aequorin luminescence, the aequorin response, indicating a rise of intracellular calcium ion concentration, Ca/. The aequorin response reached a maximum after the peak of the electrical response of the photoreceptor, decayed during a prolonged stimulus, and returned to an undetectable level in the dark. Reduction of Ca, reduced the amplitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
194
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(208 citation statements)
references
References 29 publications
13
194
1
Order By: Relevance
“…The quantitatively disparate contribution of Ca influx to the photocurrent and its variable role as a modulatory factor may be related to the different mechanisms underlying the increase in cytosolic Ca that accompanies the photoresponse. In Limulus, the light-induced Ca transient survives superfusion with 0-Ca, implying that it is mostly due to internal release (Brown and Blinks, 1974). Because the peak concentration in the rhabdomeric lobe can reach tens of micromolar (Brown et al, 1977;Levy and Fein, 1985;Ukhanov et al, 1995), any additional Ca permeating through light-activated channels would not be expected to exert a major influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitatively disparate contribution of Ca influx to the photocurrent and its variable role as a modulatory factor may be related to the different mechanisms underlying the increase in cytosolic Ca that accompanies the photoresponse. In Limulus, the light-induced Ca transient survives superfusion with 0-Ca, implying that it is mostly due to internal release (Brown and Blinks, 1974). Because the peak concentration in the rhabdomeric lobe can reach tens of micromolar (Brown et al, 1977;Levy and Fein, 1985;Ukhanov et al, 1995), any additional Ca permeating through light-activated channels would not be expected to exert a major influence.…”
Section: Discussionmentioning
confidence: 99%
“…(Millecchia and Mauro, 1969;Brown and Mote, 1974); by contrast, a significant shift was reported in Balanus photoreceptors (Brown et al, 1971). A complementary observation in these two species is that the intracellular rise in Ca that accompanies the light response was drastically reduced in low-Ca external solution in Balanus but was only attenuated in Limulus (Brown and Blinks, 1974), suggestive of differences in the extent to which Ca influx may occur during the photoresponse.…”
Section: Introductionmentioning
confidence: 96%
“…Less elaborate, but also well developed, are Ca2+-sequestering sub-surface cisternae associated with the nonreceptive plasma membrane areas of the cell (43) . These two prominent high-affinity Ca"-buffering SER elements thus possess a strategic position relative to the cell periphery where stimulus-induced changes of Cai+ (6,8,9,26) most probably take place.…”
Section: Comparative Aspectsmentioning
confidence: 99%
“…The Ca pump has a high affinity for Ca 2+ ions : the threshold for activation of the pump is -5 X 10 -8 M, the apparent KM,c,, is -4 X 10 -7 M . When Na' or Li + is substituted for K+ , Ca uptake rate is decreased by 40-50% .The results show that the Ca t+ -sequestering SER in leech photoreceptors shares some basic properties with skeletal muscle sarcoplasmic reticulum and supports the idea that certain subregions of the SER in invertebrate photoreceptors function as effective Ca 2+ sinks/buffers close to the plasmalemma.Direct evidence from measurements with Ca 2+ indicators (6,8,9,26) and Ca'-sensitive microelectrodes (6), as well as indirect evidence from electrophysiological experiments (see, for example, references 1,15,24,25,35), suggest that the free calcium concentration (Caû,+) in the cytosol of photoreceptor cells of invertebrates increases upon illumination. Several laboratories have shown that this light-induced increase of Cap' modulates the adaptational state of the cells (see reference 7 for review), a Cat+-dependent potassium conductance (see, for example, reference 17, 18, 38), and mediates the light-induced pigment granule migration in fly photoreceptors (22) .…”
mentioning
confidence: 99%
See 1 more Smart Citation